Las na gruncie porolnym – oczekiwania i rzeczywistość - Krawczyk, Robert; Kowalczuk, Sylwester; Ksepko, Marek; Sierota, Zbigniew (Leśne Prace Badawcze, 2021)
In Central Europe, deforestation led to a reduction of forest area by almost 80%, compared to the original area, by the beginning of the 20 th century. At this point in time, a period of intensive reforestation began in an effort to restore forest areas. This process of reforestation, especially on post-agricultural land, continues to this day. This article examines reforestation and natural regeneration on former farmland and the factors that influence the current state as well as the future growth of the forest. Ancient and contemporary views on the functioning of stands on post-agricultural land created by both, natural and forced succession (i.e. afforestation), are recalled. In Poland, this issue primarily concerns managed state forests, which cover an area of over 2 million hectares. We discuss the differences in the development of these stands resulting from the history of agricultural cultivation, the type of afforestation, the influence of environmental factors as well as biotic threats to their development. Furthermore, the need to change the silviculture-, protection- and endowment-based approach to forest management in stands on post-agricultural land is highlighted.